Integrative approach to model creation of specialist’s speech competence (Eurasian Journal of Philology Science and Education, 2021)
The article discusses the need for an interdisciplinary approach to the creation of a modern model of specialists’ speech communication in the professional field. The purpose of this article is to determine the level of speech culture of specialists, which has a huge influence on their professional formation and self-realization in modern society, through the synthesis of various scientific knowledge and computer technologies. The work describes in detail modeling techniques of specialist’s professional communication, provides an analysis of previous models, their features. Based on a generalization of scientific literature, the meaning of the concept of "model" is revealed. The authors believe that in the process of developing a model of communicants in professional activity, it is necessary to take into account all external and internal factors of communication. The authors emphasize that work on improving the model of specialists’ speech competence will be continued within the framework of a scientific project. The effectiveness and prospects of the integrative approach in the study of speech competence, including mathematical methods and computer programs, are justified, which will make it possible to develop a clear algorithm of consistent actions necessary to accurately measure the level of speech culture of a specialist who will affect the improvement of the professional image and demand of the specialist. According to the authors, this model contributes to the formation of key competencies of a competitive specialist; ensure the development of personal growth.Key words: integrative approach, communication, model, speech competence, professional activity.